Muatan Islam Moderat dalam Mata Kuliah Pendidikan Agama Islam di Prodi Teknik Pertambangan UPN Veteran Yogyakarta - Abrori, M. Sayyidul; Raharjo, Fajar Fauzi; Lailiy, Nuriyah (Ta'allum: Jurnal Pendidikan Islam, 2019)
This research is focused on moderat Islam content in Islamic Education Subject at Mining Engineering Program, Faculty of Mineral Technology, UPN Veteran Yogyakarta.  The radicalism at several Indonesian college must be opposed by the moderation of Islam. Islamic Education, as a compulsory subject, has a strategic role to against radicalism at college by moderation of Islam. This research is a field research by qualitative approach. Documentation and interview are the metode of this research. The results of this research indicate that Islamic education subject in Mining Engineering Program contains moderate Islam both in its objectives and material. Moderate Islam is packaged in lecture material by means of contextualization and integration with the latest issues such as tolerance, humanity, human rights and democracy in every material. In addition, PAI lecturers implement Islamic moderation by using three methods, which are broad-minded, opened and make Islamic teachings easy to practice. In this way, the Mining Engineering program can prevent radicalism. This is proven by not including UPN Yogyakarta Veterans in the list of PTN that are exposed to radicalism.